2017
DOI: 10.1016/j.dnarep.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

POLB: A new role of DNA polymerase beta in mitochondrial base excision repair

Abstract: The mitochondrial genome is a matrilineally inherited DNA that encodes numerous essential subunits of the respiratory chain in all metazoans. As such mitochondrial DNA (mtDNA) sequence integrity is vital to organismal survival, but it has a limited cadre of DNA repair activities, primarily base excision repair (BER). We have known that the mtDNA is significantly oxidized by both endogenous and exogenous sources, but this does not lead to the expected preferential formation of transversion mutations, which sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 23 publications
(26 reference statements)
0
23
0
Order By: Relevance
“…The Polγ holoenzyme is a heterotrimer consisting of two identical accessory subunits (Polγ-B) and one catalytic subunit (Polγ-A), where the accessory subunits enhance the processivity and catalytic function of Polγ-A (Gray and Wong, 1992;Johnson et al, 2000;Carrodeguas et al, 2002;reviewed in Kaguni, 2004). Until recently, Polγ was thought to be the sole polymerase within the mitochondrion that was responsible for both mtDNA replication and repair; however, at least four other DNA polymerases have been noted to play a role in mtDNA maintenance namely, DNA polymerase beta, PrimPol, polymerase theta, and polymerase zeta (Singh et al, 2015;Wisnovsky et al, 2016;Sykora et al, 2017;Bailey et al, 2019;reviewed in Bailey and Doherty, 2017;Kaufman and Van Houten, 2017;Krasich and Copeland, 2017). Until recently, Polγ was thought to be the sole polymerase within the mitochondrion that was responsible for both mtDNA replication and repair; however, at least four other DNA polymerases have been noted to play a role in mtDNA maintenance namely, DNA polymerase beta, PrimPol, polymerase theta, and polymerase zeta (Singh et al, 2015;Wisnovsky et al, 2016;Sykora et al, 2017;Bailey et al, 2019;reviewed in Bailey and Doherty, 2017;Kaufman and Van Houten, 2017;Krasich and Copeland, 2017).…”
Section: Mtdna Replicationtranscription and Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…The Polγ holoenzyme is a heterotrimer consisting of two identical accessory subunits (Polγ-B) and one catalytic subunit (Polγ-A), where the accessory subunits enhance the processivity and catalytic function of Polγ-A (Gray and Wong, 1992;Johnson et al, 2000;Carrodeguas et al, 2002;reviewed in Kaguni, 2004). Until recently, Polγ was thought to be the sole polymerase within the mitochondrion that was responsible for both mtDNA replication and repair; however, at least four other DNA polymerases have been noted to play a role in mtDNA maintenance namely, DNA polymerase beta, PrimPol, polymerase theta, and polymerase zeta (Singh et al, 2015;Wisnovsky et al, 2016;Sykora et al, 2017;Bailey et al, 2019;reviewed in Bailey and Doherty, 2017;Kaufman and Van Houten, 2017;Krasich and Copeland, 2017). Until recently, Polγ was thought to be the sole polymerase within the mitochondrion that was responsible for both mtDNA replication and repair; however, at least four other DNA polymerases have been noted to play a role in mtDNA maintenance namely, DNA polymerase beta, PrimPol, polymerase theta, and polymerase zeta (Singh et al, 2015;Wisnovsky et al, 2016;Sykora et al, 2017;Bailey et al, 2019;reviewed in Bailey and Doherty, 2017;Kaufman and Van Houten, 2017;Krasich and Copeland, 2017).…”
Section: Mtdna Replicationtranscription and Repairmentioning
confidence: 99%
“…The DNA helicase, TWINKLE, forms a hexameric donut-shaped structure and is required at the replication fork where it functions ahead of Polγ and unwinds the DNA template for replication (Korhonen et al, 2004;Milenkovic et al, 2013;Fernández-Millán et al, 2015). Until recently, Polγ was thought to be the sole polymerase within the mitochondrion that was responsible for both mtDNA replication and repair; however, at least four other DNA polymerases have been noted to play a role in mtDNA maintenance namely, DNA polymerase beta, PrimPol, polymerase theta, and polymerase zeta (Singh et al, 2015;Wisnovsky et al, 2016;Sykora et al, 2017;Bailey et al, 2019;reviewed in Bailey and Doherty, 2017;Kaufman and Van Houten, 2017;Krasich and Copeland, 2017). mtDNA transcription is still an active area of research as several unknown variables related to initiation, elongation, and termination remain to be elucidated.…”
Section: Mtdna Replicationtranscription and Repairmentioning
confidence: 99%
“…In mammals, DNA Polβ is known to be a key enzyme in the nuclear BER pathway, whereas the DNA polymerase involved in the mitochondrial BER pathway appears to be Polγ. However, recently Polβ was identified as a mtDNA polymerase involved in mtDNA maintenance and required for mitochondrial homeostasis in cells from several different mammalian species (Kaufman and Van Houten , Sykora et al ). Interestingly, in the parasite Trypanosoma brucei , a homolog of Polβ was reported to be solely responsible for the repair and replication of mtDNA (Saxowsky et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it is noteworthy that mtDNA repair requires DNA polymerases other than DNA polymerase gamma. For instance, it has been shown that DNA polymerase beta and PrimPol, a DNA A c c e p t e d M a n u s c r i p t primase-polymerase, are able to participate to mtDNA repair in addition to their usual role in nuclear DNA repair (Kaufman and Van Houten, 2017;Torregrosa-Muñumer et al, 2017). DNA polymerases theta and zeta could also play a significant role in mtDNA maintenance .…”
Section: Mtdna Repairmentioning
confidence: 99%